Economic policy uncertainty, cost of capital, and corporate innovation - Xu, Zhaoxia (Journal of Banking & Finance, 2020)
We examine the impact of government economic policy uncertainty (GEPU) on corporate innovation and identify a cost-of-capital transmission channel. We find that GEPU increases firms’ cost of capital, which translates into lower innovation. As economic policy uncertainty rises, firms with more exposure to such uncertainty face a higher weighted average cost of capital and innovate less. Innovations of financially constrained firms and firms relying on external finance in a competitive environment are affected more. Our study provides novel evidence that higher economic policy uncertainty hinders innovation not only through the traditional investment irreversibility channel, but also through the cost-of-capital channel.